Insersi Pendidikan Anti Korupsi dalam Mata Kuliah Pendidikan Pancasila di Sekolah Tinggi Agama Islam Raudhatul Ulum - Fitri Susanty (LP3M Universitas Al-Qur'an Ittifaqiah Indralaya, 2022)
Cases of corruption in Indonesia have been rampant since the New Order era and had a negative impact on the economic, social and political life of the Indinesian people.It it is not stopped or minized, it will damage various structures of state life and national character. So it is necessary to instill the values of Anti-corruption Education, especially at the tertiary level. The purpose of this study is ti fond out how anti-corruption education material can be embadded in mandatory Five Principles Education courses at universities or colleges, especially at Raudhatul Ulum Islamic High School and to be able to know and understand the urgency of anti-corruption education when it is included in the content. The Five Principles Education course which is a general compulsary subject in tertiary institutions, and this is a small step so that anti-corruption education materialcab ne instilled and can be provided continousky and sustainably in tertiary institutions. This research uses descriptive theoretical analysis or qualitative research which is descriptive in nature and tends to be more analytical. The purpose of decriptive research is to make systematic, factual and accurate descriptions, pictures or drawings of facts, characteristics and relationships between phenomena investigated.from the result of in-depth interviews with the head of the study program at Raudhatul Ulum Islamic High School and from input during the group discussion forum by the resourceperson entitled insertion of Anti-Corruption Education in Five Principles Education Subjects in higher education, it was concluded that Raudhatul Ulum Islamic High School at basically have the same perception about it is very possible for anti-corruption education to be inserted into Five Princiles Education course, the Raudhatul Ulum Islamic High School provides additions regarding anti-corruption education which is inserted in Five Principles sourses, the chair of the study program and also input from sources is also possible to include anti-corruption education in the Five Principles general compulsary course.